2012
DOI: 10.1016/j.taap.2011.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate (EGCG) protects against chromate-induced toxicity in vitro

Abstract: Hexavalent chromium [Cr(VI)] is a human carcinogen that results in the generation of reactive oxygen species (ROS) and a variety of DNA lesions leading to cell death. Epigallocatechin-3-gallate (EGCG), the major polyphenol present in green tea, possesses potent antioxidative activity capable of protecting normal cells from various stimuli-induced oxidative stress and cell death. Here we demonstrated that co-treatment with EGCG protected human normal bronchial epithelial BEAS-2B cells from Cr(VI)-induced cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 78 publications
1
22
0
Order By: Relevance
“…Inhibition of metal induced carcinogenesis by a dietary antioxidant is a novel approach. Studies have demonstrated that co-treatment with Epigallocatechin-3-gallate (EGCG), the major polyphenol present in green tea, protected BEAS-2B cells from Cr(VI)-induced cell death in a dose-dependent manner (Wu et al , 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of metal induced carcinogenesis by a dietary antioxidant is a novel approach. Studies have demonstrated that co-treatment with Epigallocatechin-3-gallate (EGCG), the major polyphenol present in green tea, protected BEAS-2B cells from Cr(VI)-induced cell death in a dose-dependent manner (Wu et al , 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Protective effect of EGCG against SNP-induced apoptosis in L-132 human lung epithelial cells was exerted by regulating the expression of Bax and Bcl-2 as well as the activity of caspase-3 [16]. EGCG protected the BEAS-2B cells from chromate-induced toxicity by reducing ROS levels as well as by inhibiting the expression of apoptosis-related genes [18]. The protective properties of EGCG on toxic chemical-induced apoptosis are associated with its ability to upregulate transcription factors such as Nrf2 [19] or prevent the degradation of positive growth effectors such as HIF-1 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it was previously described the dietary intervention of polyphenols in cancer prevention, including the chemopreventive ability of dietary flavonoids, act against lung carcinogens. In vitro studies were performed over a wide range of polyphenols which showed significant effect in lung Cancer, such as epigallocatechin-3-gallate (EGCG), suppresses in a dose dependent manner, the hexavalent chromium (Cr (VI))-induced apoptosis, reduces activation of caspase-3 and nuclear poly (ADP-ribose) polymerase (PARP), and intracellular ROS [9]. It has also been demonstrated, that Caffeic acid can scavenge intracellular ROS and hence prevent lipid peroxidation in WI-38 cells [10].…”
Section: Introductionmentioning
confidence: 99%